Determining the role of music attitude and its precursors in stimulating the psychological wellbeing of immigrants during COVID quarantine – a moderated mediation approach - Wang, Xiaokang; Huang, Wenrong (Frontiers in Psychology, 2023)
Based on social cognitive theory (SCT), the purpose of this study is to examine the role of music attitude and its essential precursors in stimulating the psychological wellbeing of immigrants in isolation (quarantine) during the COVID pandemic. This study employed quantitative methodology; an online survey was administered to collect sufficient data from 300 immigrants who traveled to China during the pandemic. Data were collected from five centralized quarantine centers situated in different cities in China. Additionally, the valid data set was analyzed using structural equation modeling (SEM) via AMOS 24 and SPSS 24. The results indicate that potential predictors such as cognitive - music experience (MEX), environmental - social media peer influence (SPI), and cultural factors such as native music (NM) have a direct, significant, and positive effect on music attitude (MA), which further influences immigrants’ psychological wellbeing (PW) during their quarantine period. Moreover, in the presence of the mediator (MA), the mediating relationships between MEX and PW, and NM and PW, are positive, significant, and regarded as partial mediation. However, the moderated mediation effects of music type (MT) on MEX-MA-PW and NM-MA-PW were found to be statistically not significant and unsupported. This study contributes to the literature on the effectiveness of individuals’ music attitude and its associated outcomes, focusing on mental health care in lonely situations such as quarantine during the COVID pandemic. More importantly, this study has raised awareness about music, music attitude, and their beneficial outcomes, such as mental calmness and peacefulness for the general public, particularly during social distancing, isolation, and quarantine in the COVID pandemic situation.